2008
DOI: 10.1057/palgrave.jibs.8400348
|View full text |Cite
|
Sign up to set email alerts
|

The paradox of technological capabilities: a study of knowledge sourcing from host countries of overseas R&D operations

Abstract: We investigate the factors that influence the extent to which a multinational corporation's headquarters (MNC-HQ) sources knowledge from the host countries of its R&D labs. We propose that the technological capabilities held by MNC-HQs present a paradox. On the one hand, they enhance MNC-HQs' learning capabilities. On the other hand, they reduce MNC-HQs' motivations to outsource knowledge from host countries. We also argue that it is important to consider both relative and absolute levels of technological capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
121
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(125 citation statements)
references
References 43 publications
4
121
0
Order By: Relevance
“…Hierarchical relationships in innovation processes are increasingly being replaced by associations characterized by parity and reciprocity. Subsidiaries that in the past were subservient operating "arms" driven by the headquarters "brain" are now increasingly generating knowledge locally that is to be used throughout the global MNE network (Cantwell & Mudambi, 2005;Song & Shin, 2008). The level and sophistication of technology continues to rise at an ever-increasing pace.…”
Section: Co-evolution: a Dialectic Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…Hierarchical relationships in innovation processes are increasingly being replaced by associations characterized by parity and reciprocity. Subsidiaries that in the past were subservient operating "arms" driven by the headquarters "brain" are now increasingly generating knowledge locally that is to be used throughout the global MNE network (Cantwell & Mudambi, 2005;Song & Shin, 2008). The level and sophistication of technology continues to rise at an ever-increasing pace.…”
Section: Co-evolution: a Dialectic Perspectivementioning
confidence: 99%
“…Scholars have examined the points of contact of MNEs within host locations (Cantwell & Santangelo, 1999), as well as the motivations to pursue knowledge (Song & Shin, 2008). However, the conduits through which knowledge travels remain underexplored in the MNE context.…”
Section: Co-evolution: a Dialectic Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…In an attempt to analyze knowledge transfer between headquarters and subsidiaries, Song and Shin (2008) studied the process in various semiconductor manufacturers. Their research showed that MNCs that developed their own knowledge and technology paths can adopt knowledge management processes, somewhat contradicting the current trend.…”
Section: The Role Of Subsidiaries and Their Absorptive Capacitymentioning
confidence: 99%
“…Support for this perspective has come from theoretical work on the existence of multinationals without advantages (Fosfuri and Motta 1999;Siotis 1999), from empirical analysis of the motivation for FDI (Driffield and Love 2007), and from studies of the importance of knowledge flows from host countries to foreign affiliates and MNE headquarters (Singh 2007;Song and Shin 2008;Criscuolo 2009). This in turn has led to a strand of literature which is concerned not with the analysis of the determinants or effects of intra-MNE knowledge flows, but with developing suitable typologies and taxonomies of affiliates based on the nature and extent of their knowledge linkages with parents and other parts of the group structure Govindarajan 1991, 1994;Kobrin 1991;Birkinshaw and Morrison 1995;Harzing and Noorderhaven 2006).…”
Section: Introductionmentioning
confidence: 99%